1999
DOI: 10.1103/physrevb.60.10754
|View full text |Cite
|
Sign up to set email alerts
|

Band gaps and quasiparticle energy calculations on ZnO, ZnS, and ZnSe in the zinc-blende structure by theGWapproximation

Abstract: We have calculated the quasiparticle band gaps of ZnO, ZnS, and ZnSe in zinc-blende structure within the GW approximation using a full random-phase approximation dielectric matrix. The linear muffin-tin orbital basis was used for this calculation and the 3d orbitals of the Zn atom were treated as valence band in every case. The calculated band gaps are 3.59, 3.97, and 3.10 eV for ZnO, ZnS, and ZnSe, respectively. The gaps of ZnS and ZnSe are in good agreement with the experimental values and so is the gap of Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(47 citation statements)
references
References 20 publications
(27 reference statements)
10
37
0
Order By: Relevance
“…All these secondary phases have a large E g , with E g = 2.24 eV for the hexagonal SnS 2 , [ 37 ] 3.68 eV for the zinc-blende ZnS. [ 47 ] For SnS 2 , it is also reported that the band alignment with CZTSSe may induce a hole blocking layer for charge injection into the Mo-electrode. [ 37 ] Having a large E g in ZnS, it is no doubt that ZnS may act as a hole blocking layer.…”
Section: Discussion Of Secondary Phasesmentioning
confidence: 97%
“…All these secondary phases have a large E g , with E g = 2.24 eV for the hexagonal SnS 2 , [ 37 ] 3.68 eV for the zinc-blende ZnS. [ 47 ] For SnS 2 , it is also reported that the band alignment with CZTSSe may induce a hole blocking layer for charge injection into the Mo-electrode. [ 37 ] Having a large E g in ZnS, it is no doubt that ZnS may act as a hole blocking layer.…”
Section: Discussion Of Secondary Phasesmentioning
confidence: 97%
“…There are very few reports of the existence for zincblende ZnO phase at ambient conditions [10,27,28]. To the best of our knowledge, the only experimental result is the lattice constant a = 4.62 Å [28].…”
Section: Details Of Calculationmentioning
confidence: 96%
“…In addition, various computational methods have been applied in the calculation of its physical properties [2,[14][15][16]. However, further studies of this material are required, both from an application and theoretical point of view so as to determine their basic properties and exploit them in device applications.…”
Section: Introductionmentioning
confidence: 99%